Effect of clomiphene citrate on uterine hemodynamics in women with unexplained infertility - Omran E; El-Sharkawy M; El-Mazny A; Hammam M; Ramadan W; Latif D; Samir D; Sobh S (Dove Medical Press, 2018)
Eman Omran, Mohamed El-Sharkawy, Akmal El-Mazny, Mohamed Hammam, Wafaa Ramadan, Dina Latif, Dalia Samir, Sherine Sobh Department of Obstetrics and Gynecology, Kasr Al-Ainy Hospital, Cairo University, Cairo, Egypt Purpose: The aim of the study was to evaluate the effect of clomiphene citrate on uterine artery blood flow using pulsed Doppler and endometrial and subendometrial micro vascularization using 3D power Doppler in unexplained infertility. Patients and methods: In a prospective observational study at a university teaching hospital, the mid-luteal (peri-implantation) endometrial thickness and volume, uterine artery pulsatility index (PI) and resistance index (RI), endometrial and subendometrial vascularization index (VI), flow index (FI), and vascularization flow index (VFI), and serum estradiol and progesterone levels were compared between natural and clomiphene citrate stimulated cycles in the same group of 50 patients with unexplained infertility. Statistical analysis was done using paired t-test to compare different study variables. Results: The primary outcome, which was the endometrial flow index, was significantly lower in the stimulated cycles (mean ± SD: 23.89±7.96 vs 27.49±8.73, mean difference (95% CI): -3.6 (-2, -5.9); P=0.03). The mean ± SD of endometrial thickness (10.92±3.04 vs 12.46±3.08 mm; P=0.01), volume (4.57±1.28 vs 5.26±1.32 cm3; P=0.009), endometrial VI (0.86±0.15 vs 0.95%±0.21%; P=0.02), VFI (0.25±0.08 vs 0.31±0.12; P=0.004), subendometrial VI (1.93±0.68 vs 2.26%±0.75%; P=0.02), FI (26.81±9.16 vs 30.73±9.87; P=0.04), and VFI (0.68±0.18 vs 0.79±0.21; P=0.006) were significantly lower in the stimulated cycles. However, there were no significant differences in the uterine artery PI (P=0.12) and RI (P=0.08) or serum estradiol (P=0.54) and progesterone (P=0.37) levels between natural and stimulated cycles. Conclusion: Peri-implantation endometrial perfusion is significantly lower in clomiphene citrate stimulated cycles when compared to natural ones in patients with unexplained infertility. Keywords: subendometrial blood flow, 3D power Doppler, endometrial blood flow, uterine artery Doppler